2010
DOI: 10.1111/j.1472-765x.2010.02883.x
|View full text |Cite
|
Sign up to set email alerts
|

High-density polyethylene (HDPE)-degrading potential bacteria from marine ecosystem of Gulf of Mannar, India

Abstract: Aims:  Assessment of high‐density polyethylene (HDPE)‐degrading bacteria isolated from plastic waste dumpsites of Gulf of Mannar. Methods and Results:  Rationally, 15 bacteria (GMB1‐GMB15) were isolated by enrichment technique. GMB5 and GMB7 were selected for further studies based on their efficiency to degrade the HDPE and identified as Arthrobacter sp. and Pseudomonas sp., respectively. Assessed weight loss of HDPE after 30 days of incubation was nearly 12% for Arthrobacter sp. and 15% for Pseudomonas sp. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(91 citation statements)
references
References 17 publications
3
81
0
7
Order By: Relevance
“…The biofilm formation can be influenced by the cellular surface hydrophobicity (Gilan et al, 2004;Balasubramanian et al, 2010). Mineral oil has promoted the hydrophobic interaction between the fungal strains and HDPE surface.…”
Section: Resultsmentioning
confidence: 98%
“…The biofilm formation can be influenced by the cellular surface hydrophobicity (Gilan et al, 2004;Balasubramanian et al, 2010). Mineral oil has promoted the hydrophobic interaction between the fungal strains and HDPE surface.…”
Section: Resultsmentioning
confidence: 98%
“…The result revealed that all the tested sub MIC doses of silver exhibited significant biofilm attenuation property compared to control where the organism was grown and allowed to form biofilm in absence of silver (Figure 1). The extent of microbial biofilm formation on test tubes in presence and absence of silver was also measured by determining the amount of total extractable protein [22] [29]. Since it is very difficult to estimate the total microbial populations on the test tube surfaces by conventional plate counting, total protein extraction can be an alternative tool to address the extent of microbial population over there because protein can only be coming from the biotic source like bacteria and not from abiotic source like test tubes.…”
Section: Silver Shows Antibiofilm Activities Against Pseudomonas Aerumentioning
confidence: 99%
“…Annually, about 500 billion to 1 trillion polythene carrier bags are used around the globe and 25 million tons of synthetic plastics accumulate in the sea coasts and terrestrial environment every year [3]. In particular, approximately 61 thousand tons of plastic wastes found their way in to India in the year 2000 [4]. However, with these drastic rises in the use of plastic materials, a corresponding development of processes for the harmless disposal or degradation of the plastic waste has not been noticed.…”
Section: Introductionmentioning
confidence: 99%